A novel practical truss-based approach for evaluation the non-linear behavior of steel plate shear walls. (June 2022) - Moradnezhad, B.; Oghabi, M.; TahamouliRoudsari, M.; Movahednia, M.
Abstract: Nowadays steel plate shear walls (SPSW) are widely used as an effective structural system subjected to seismic loads. So far, several numerical approaches were presented to evaluate the non-linear behavior of these structures. Remarkably simplifications accomplished by researchers to performance-based design purposes, but the implementation of a practical method in commercial code to engineers' utilization still remained a challenge. In this paper, a simplified approach based on (1D) truss elements is developed for the non-linear analysis of SPSWs. In this approach, the complicated continuous (2D) elements are substituted by two vertical elements (columns) and two diagonal rods (braces). The equivalent truss-based (ETB) system consists of continuous columns and pin-ended braces with a specific configuration. The axial and shear stiffnesses of the ETB system are provided by the axial behavior of columns and braces, respectively. A bi-linear stress–strain diagram of steel including strength drop due to buckling was adopted for ETB elements. The proposed method was benchmarked to several experimental SPSWs at the structural level. The specimens include five SPSWs with different aspect ratios in the absence or presence of openings and/or stiffeners. The obtained results by means of the novel approach including global behavior and local buckling modes compared with experimental results and available numerical predictions in the literature as well. The results proved the method is able to estimate the non-linear behavior of SPSWs in satisfactory accuracy with very limited computational cost.